THE FACTORS INFLUENCING QUALITY OF STRUCTURE OF WORKPIECES PROCESSED ON THE VACUUM LINE «MODULTHERM 7/1» - S. P. Rudenko; A. L. Valko; A. N. Chichin (Литьë и металлургия, 2017)
Results of metallographical observations of structural constituent of carburized cases and a core of gears after thermochemical treatment on a vacuum line «ModulTherm 7/1» made by corporation «ALD Vacuum Technologies GmbH» are given. It was established that the cause of formation of non martensitic transformations of austenite in carburized cases and in a core of workpieces is insufficient cooling capacity of the hardening module of a vacuum line «ModulTherm 7/1».